Antibacterial activity in vitro of the extract etanòlico of annona muricata (graviola) on streptococcus mutans and lactobacilus - Eliana Guillén Fernández (2019)
The objective of the pilot study was to demonstrate the active principles in the leaves of Annona muricata, assess their antibacterial properties on culture media of S. mutans and Lactobacillus obtained from cavities of children with early childhood caries, who were assisted in dental clinic, and evaluate which of the two studied strains presents better antibacterial power. The results of this research are intended to contribute to the development of a new antibacterial agent of vegetal origin, which is used to prepare products of lower toxicity than conventional ones used for control of dental decay in children.We evaluated the active ingredients of the leaves of Annona ethanolic extract muricata L. (Graviola),using fine layer chromatiography to ethanol concentrations subject to a Rotary evaporator and column with silica gel. Then, We determined the antimicrobial potential through in vitro susceptibility testing.